Antioxidant and Anti-aging Activities from Zodia (Evodia suaveolens J.R. Forst & G. Forst) Fruit and Leaf Extract - Greesty F. Swandiny; Yesi Desmiaty; Haura Usna Rahmah (Tropical Biopharmaca Research Center, IPB University, 2022)
Aging is a natural process that occurs in every living organism, including humans. Skin wrinkle, caused by deterioration activity of the elastase enzyme, is one example of the aging process. The activity of the elastase enzyme could be inhibited by flavonoid and phenolic compounds. Zodia (Evodia suaveolens) from the family of Rutaceae is one of the indigenous Indonesian plants widely known as rich in flavonoid and phenolic compounds. The purpose of this study is to explore antioxidant and anti-aging activity from ethanolic extract of fruit and leaf Zodia. The extracts were prepared by refluxing fruit and leaf zodia in 96% ethanol. The obtained extracts were characterized for the phytochemical constituent and its antioxidant activity determined using the 2,2-diphenyl-1-picrylhydrazyl method as well as anti-elastase activity for anti-aging evaluation. Phytochemical analysis of both samples showed the presence of flavonoids, saponins, tannins, steroids and essential oils. The calculation of IC50 in antioxidant activity using the DPPH method showed that ethanolic extract of zodia leaf (264.15 ppm) was higher compared to fruit extract (121.59 ppm). The fruit extract was further tested for anti elastase activity with IC50 of 145.67 ppm. In conclusion, the presence of phytochemicals in zodia fruit may be responsible for the antioxidant and anti-aging activities.